Derechos sobre bienes y el numerus clausus - Mejorada Chauca, Martín (2014)
At every moment, persons are in contact withg oods that serve to satisfy the different needsencountered in daily life. Since the relations between persons and goods are an importantmatter, it is basic to understand the area of Civil Law that regulates them: the Rights inRem. However, we find that, from the relations that a person may establish with goods, notall of them are considered to be part of sucharea, but only a limited number.In this article, the author proposes to abandon the idea that the only Rights in Rem are the ones expressly set as them by the law, reminding that the persons themselves are the ones that can make the best decision about which relation is more  convenient for them to establish with a good, since the interest that wants to be satisfied depends on each person.